Neutrophil to lymphocyte ratio and cardiovascular diseases: a review. (January 2013) - Bhat, Tariq; Teli, Sumaya; Rijal, Jharendra; Bhat, Hilal; Raza, Muhammad; Khoueiry, Georges; Meghani, Mustafain; Akhtar, Muhammad; Costantino, Thomas
The role of inflammatory markers in cardiovascular diseases has been studied extensively and a consistent relationship between various inflammatory markers and cardiovascular diseases has been established in the past. Neutrophil to lymphocyte ratio (NLR) is a new addition to the long list of these inflammatory markers. NLR, which is calculated from complete blood count with differential, is an inexpensive, easy to obtain, widely available marker of inflammation, which can aid in the risk stratification of patients with various cardiovascular diseases in addition to the traditionally used markers. It has been associated with arterial stiffness and high coronary calcium score, which are themselves significant markers of cardiovascular disease. NLR is reported as an independent predictor of outcome in stable coronary artery disease, as well as a predictor of short- and long-term mortality in patients with acute coronary syndromes. It is linked with increased risk of ventricular arrhythmias during percutaneous coronary intervention (PCI) and higher long-term mortality in patients undergoing PCI irrespective of indications of PCI. In patients admitted with advanced heart failure, high NLR was reported with higher inpatient mortality. Recently, NLR has been reported as a prognostic marker for outcome from coronary artery bypass grafting and postcoronary artery bypass grafting atrial fibrillation.